A barometric approach for high temperature water desorption isotherm determination. (April 2021) - Linke, Tobias; Kirsch, Roman; Kohlus, Reinhard
Abstract: Sorption isotherms give an insight into thermodynamic behaviour of materials during drying. This is necessary for process optimization and to prevent over-processing, especially at higher temperatures, such as in drum drying or superheated steam spray drying. Aim of this study is to introduce a simple, barometric method for the determination of water desorption isotherms. As test materials, microcrystalline cellulose and potato starch are used. Both materials show specific temperatures where the trend of the determined GAB parameters and the slope of the isosteric heat of sorption are changing significantly. Thus, is the predictability of thermodynamic behaviour depending on the material. Further, it is demonstrated that the extrapolation of low temperature sorption data (<60 °C) leads to an error in prediction of 30% for microcrystalline cellulose and 15% for potato starch, compared to isothermal data determined at the respective temperature by the barometric method. Reducing the measurement time for the presented barometric pressure approach would extend its application range to temperature sensitive materials, if short residence time processes such as spray drying are of interest. Highlights: Introduction of a simple barometric method for desorption isotherm determination. Coverage of elevated temperature from 60 to 140 °C over a wide water activity range. Determination of appropriate drying process parameters at corresponding temperature. Data measured at >80 °C deviate from commonly extrapolated low temperature isotherms.